Use of virtual slide system for quick frozen intra-operative telepathology diagnosis in Kyoto, Japan - Nakano Kooji; Takashima Tooru; Hashimoto Yukimasa; Takamatsu Terumasa; Tsuchihashi Yasunari; Fujita Setsuya (BMC, 2008)
Abstract We started to use virtual slide (VS) and virtual microscopy (VM) systems for quick frozen intra-operative telepathology diagnosis in Kyoto, Japan. In the system we used a digital slide scanner, VASSALO by CLARO Inc., and a broadband optic fibre provided by NTT West Japan Inc. with the best effort capacity of 100 Mbps. The client is the pathology laboratory of Yamashiro Public hospital, one of the local centre hospitals located in the south of Kyoto Prefecture, where a fulltime pathologist is not present. The client is connected by VPN to the telepathology centre of our institute located in central Kyoto. As a result of the recent 15 test cases of VS telepathology diagnosis, including cases judging negative or positive surgical margins, we could estimate the usefulness of VS in intra-operative remote diagnosis. The time required for the frozen section VS file making was found to be around 10 min when we use ×10 objective and if the maximal dimension of the frozen sample is less than 20 mm. Good correct focus of VS images was attained in all cases and all the fields of each tissue specimen. Up to now the capacity of best effort B-band appears to be sufficient to attain diagnosis on time in intra-operation. Telepathology diagnosis was achieved within 5 minutes in most cases using VS viewer provided by CLARO Inc. The VS telepathology system was found to be superior to the conventional still image telepathology system using a robotic microscope since in the former we can observe much greater image information than in the latter in a certain limited time of intra-operation and in the much more efficient ways. In the near future VS telepathology will replace conventional still image telepathology with a robotic microscope even in quick frozen intra-operative diagnosis.